Effect of Methamphetamine Addiction on Brain Chemistry Through the Adoption of Fractalkine as an Indicator (Indian Journal of Forensic Medicine & Toxicology, 2020)
Methamphetamine (METH), a highly addictive drug and a strong stimulant of the central nervous system.METH abuse is increasing, especially among young people and adolescents, and therefore we wanted in thisresearch to shed light on some of the problems resulting from meth use, especially its effect on the centralnervous system, the blood-brain barrier, and Fractalkine (CX3CL1).CX3CL1 is the only member of the CX3C subcategory of chemokines, which have a major role in thecentral nervous system by regulating interactions between neurons, glial cells, and immune cells. It is alsoconsidered heavily involved in traumatic brain injury (TBI) and spinal cord injury (SCI).The study was conducted on eighty people divided into three groups, thirty non addicted men as a controlgroup(G1), taking into account and excluding, cigarette smoking, age, social and cultural conditions, andchronic diseases, also thirty people addicted to methamphetamine(G2), and twenty people addicted tomethamphetamine and other narcotic substances (mix)(G3), whose ages ranged between (15-45) years andthe period of methamphetamine abuse ranged between (1-7) years.The results of study showed that CX3CL1 values were higher among addicted persons compared to nonaddicts (G1), this difference in values shows us the effect of meth on the total values of CX3CL1.